Advanced glycation end products in diabetic retinopathy and phytochemical therapy - Kang, Qingzheng; Dai, Haiyu; Jiang, Suwei; Yu, Li (Frontiers in Nutrition, 2022)
Advanced glycation end products (AGEs) are generated by the nonenzymatic glycation of proteins or lipids. Diabetic retinopathy (DR) is one common complication in patients with diabetes. The accumulation of AGEs in retinal cells is strongly associated with the development of DR. AGEs can induce the breakdown of redox balance and then cause oxidative stress in retinal cells, exerting cytopathic effects in the progression of DR. The interaction between AGEs and the receptor for AGE (RAGE) is involved in multiple cellular pathological alterations in the retina. This review is to elucidate the pathogenetic roles of AGEs in the progression of DR, including metabolic abnormalities, lipid peroxidation, structural and functional alterations, and neurodegeneration. In addition, disorders associated with AGEs can be used as potential therapeutic targets to explore effective and safe treatments for DR. In this review, we have also introduced antioxidant phytochemicals as potential therapeutic strategies for the treatment of DR.